The Family of Francis Marion Shaw Newsletter Volume 8 Number 3 - Shaw, Bryan Lee (My University, 1999)
This newsletter profiles Charles Bruner Shaw, Sr., detailing a life marked by early family tragedy, resilience, and a dedicated career in law enforcement. Born in 1888, he was orphaned young and raised by his grandparents, Francis Marion and Rachel Shaw. Despite personal sorrows, including the deaths of his first wife and an infant daughter, Bruner pursued a lifelong passion for law enforcement, influenced by his cousins who were also peace officers. He rose through the ranks from deputy to Chief of Police in various towns across Georgia and Florida, gaining a reputation for courage in confronting illicit liquor stills, gambling operations, and dangerous criminals. His exploits included being shot at by a fugitive, an assault by a prisoner, leading moonshine raids, and notably capturing the "Bootleg Queen" after a six-mile chase. Despite his success and daring, Bruner and his family frequently moved due to meager pay, and he sometimes had to supplement his income or leave police work entirely, notably working in the citrus industry during the Depression. After decades of service, he continued to work as a security officer and fish market operator before his death in 1950 from strokes at the age of 62.
This item contains 1 PDF with 8 pages with an additional 8 JP2 files
Keywords: Berrien County Historical Foundation (Nashville; Ga.); Nashville (Ga.); Berrien County (Ga.); Newsletters; Periodicals; Berrien County (Ga.)--History--Sources; Electronic records; Grady County (Ga.)--History; Historic preservation--Georgia--Berrien County; Georgia--Genealogy